Hydraulic composition, mortar composition, and cured mortar

The hydraulic composition, featuring a blend of Portland cement and other additives, addresses the strength deficiencies in existing restoration materials by producing a mortar cured body with improved strength and reduced water absorption, suitable for structural repairs.

JP2025062039AInactive Publication Date: 2025-04-11MU MATEX CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025016082
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-03
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing cross-sectional restoration materials lack sufficient strength for structural applications, despite efforts to improve aesthetic appearance and durability.

Method used

A hydraulic composition comprising Portland cement, fine calcium carbonate powder, fine aggregate, inorganic expander, fluidizing agent, shrinkage reducing agent, antifoaming agent, re-emulsified resin powder, and alkyl silicone resin-based water repellent, which forms a mortar cured body with excellent workability, strength development, and water absorption suppression.

Benefits of technology

The hydraulic composition enables the creation of a mortar cured body with enhanced strength, particularly in bending and compressive strength, while effectively suppressing water absorption, making it suitable for repairing concrete structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062039000001
    Figure 2025062039000001
  • Figure 2025062039000002
    Figure 2025062039000002
  • Figure 2025062039000003
    Figure 2025062039000003
Patent Text Reader

Abstract

To provide a hydraulic composition that has excellent workability and can form cured mortar having highly developed strength and reduced amounts of water absorption, and a mortar composition.SOLUTION: A hydraulic composition contains Portland cement, calcium carbonate fine powder, fine aggregate, an inorganic expansive additive, a superplasticizer, a shrinkage reducer, an antifoamer, re-emulsified resin powder and an alkyl silicone resin-based water-repellent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hydraulic composition, a mortar composition and a hardened mortar used in various construction works in the fields of civil engineering and construction. [Background technology]

[0002] Concrete used in various structures is inherently highly durable, but may deteriorate in parts depending on the structure or environment in which it is used. Such deterioration can cause the concrete to lose strength, and so it must be repaired. When repairing, the deteriorated area is removed, and then a cross-section repair material such as a mortar composition is used.

[0003] Patent Document 1 discloses a cross-section repair material that contains (A) white cement, (B) fine aggregate, (C) metakaolin, (D) a hygroscopic clay mineral, (E) a silane-based water repellent, and (F) a polymer, and is characterized in that both (B) and (D) have a chroma of 0.5 or less and a value of 9 or more in the Munsell color system.

[0004] Patent Document 2 discloses a cross-section repair material that contains (A) white cement, (B) ordinary fine aggregate having a chroma of 0.5 to 1.0 and a value of 8.5 to 9.5 in the Munsell color system, (C) metakaolin, (D) a hygroscopic clay mineral having a chroma of 0.1 to 1.0 and a value of 8 to 9.5 in the Munsell color system, (E) a silane-based water repellent, and (F) a polymer dispersion and / or a re-emulsifiable powdered resin. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2013-095615 A [Patent Document 2] JP 2017-114735 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the cross-section repair materials described in Patent Documents 1 and 2 are intended to improve aesthetics such as shapeability and stain resistance, and neither of them has sufficient strength required for use in structures.

[0007] Therefore, a main object of the present invention is to provide a hydraulic composition and a mortar composition which have good workability and are capable of forming a hardened mortar having excellent strength development and water absorption suppression. [Means for solving the problem]

[0008] As a result of intensive research to achieve the above-mentioned object, the present inventors have found that a hydraulic composition containing Portland cement, calcium carbonate fine powder, fine aggregate, inorganic expansive agent, fluidizing agent, shrinkage reducing agent, antifoaming agent, re-emulsifiable resin powder and alkyl silicone resin-based water repellent agent has good workability and is capable of forming a hardened mortar having excellent strength development and water absorption suppression, and have completed the present invention.

[0009] One aspect of the present invention relates to a hydraulic composition comprising Portland cement, calcium carbonate fine powder, fine aggregate, an inorganic expansive agent, a fluidizing agent, a shrinkage reducing agent, an antifoaming agent, a re-emulsifiable resin powder, and an alkyl silicone resin water repellent.

[0010] According to the hydraulic composition of one aspect of the present invention, a mortar composition having good workability can be prepared. In addition, a mortar hardened body having excellent strength development (particularly bending strength) and water absorption suppression can be formed. That is, a mortar composition is prepared by mixing and kneading the hydraulic composition with water, and the mortar composition is applied to the surface or cross section of a concrete structure, and is hardened and integrated to obtain a concrete structure having excellent strength development and water absorption suppression. Thus, the reason why the hydraulic composition of one aspect of the present invention has excellent strength development and water absorption suppression is not necessarily clear, but the present inventors believe that one of the reasons is that the inclusion of an alkyl silicone resin-based water repellent agent produces an effect similar to that of a silane coupling agent that bonds inorganic materials and organic materials.

[0011] Preferred embodiments of the hydraulic composition are (1) and (2) below. These embodiments may be combined as appropriate.

[0012] (1) The inorganic expansive material is preferably a quicklime-gypsum based expansive material. The content of the inorganic expansive material is preferably 4 to 20 parts by mass per 100 parts by mass of Portland cement. This tends to ensure excellent strength development and water absorption suppression, and to form a mortar hardened body that is excellent in dimensional stability and has sufficient adhesion durability when integrated with a concrete structure.

[0013] (2) The content of the alkyl silicone resin-based water repellent is preferably 0.01 to 3.00 parts by mass per 100 parts by mass of Portland cement, which suppresses water absorption, ensures excellent strength development, and tends to adequately maintain compressive strength in addition to bending strength.

[0014] Another aspect of the present invention relates to a mortar composition. The mortar composition contains the above hydraulic composition and water. Since the mortar composition contains the above hydraulic composition, it has good workability and can form a mortar hardened body excellent in strength development and water absorption suppression. Therefore, it can be suitably used as a repair mortar.

[0015] The unit volume mass of the mortar composition is preferably 2.05 to 2.25 kg / L. When the unit volume mass of the mortar composition is in this range, the mortar composition can obtain an appropriate compressive strength for integration with a concrete structure while maintaining good workability.

[0016] Another aspect of the present invention relates to a hardened mortar. The hardened mortar is a hardened product of the above-mentioned mortar composition. When integrated with concrete, the hardened mortar exhibits strength development and water absorption suppression, and is therefore suitable as a repair material for deteriorated concrete. Effect of the Invention

[0017] According to the present invention, there are provided a hydraulic composition and a mortar composition which have good workability and can form a hardened mortar having excellent strength development and water absorption suppression. Therefore, the hydraulic composition of the present invention can be suitably used for repairing a cross section of concrete. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.

[0019] <Hydraulic composition> The hydraulic composition of one embodiment includes Portland cement, calcium carbonate fine powder, fine aggregate, inorganic expansive agent, fluidizing agent, shrinkage reducing agent, antifoaming agent, re-emulsified resin powder, and alkyl silicone resin water repellent. Each component will be described in detail below.

[0020] Portland cement is a common hydraulic material, and any commercially available product can be used. Among these, Portland cements specified in JIS R 5210:2019 can be selected and used. From the viewpoint of workability, it is preferable to use ordinary Portland cement or high-early-strength Portland cement.

[0021] The Blaine specific surface area of ​​Portland cement is preferably 2800 to 5000 cm 2 / g, and more preferably 2900 to 4000 cm 2 / g, and more preferably 3000 to 3500 cm 2 / g. The Blaine specific surface area of ​​Portland cement is determined in accordance with JIS R 5201:1997. Portland cement having a Blaine specific surface area within the above preferred range tends to have excellent workability (workability).

[0022] The calcium carbonate fine powder may be any of the ordinary commercially available ones. Among them, it is preferable to use calcium carbonate fine powder (Kansuiseki powder) having a high whiteness.

[0023] The calcium carbonate fine powder preferably has a mass fraction (%) of particles having a particle diameter of 150 μm or more and less than 300 μm of less than 20%, and a mass fraction (%) of particles having a particle diameter of 75 μm or more and less than 150 μm of 10 to 50%. By containing calcium carbonate fine powder having a particle diameter in the above range, the hydraulic composition of the present embodiment can ensure a sufficient time for applying the mortar composition and can obtain good strength.

[0024] In addition, it is preferable that the fine powder of calcium carbonate does not contain particles having a particle size of 300 μm or more, which tends to result in good strength development.

[0025] The particle size of the calcium carbonate fine powder can be measured using several sieves with different nominal openings as specified in JIS Z 8801-1:2019 "Test sieves - Part 1: Metal mesh sieves". In this specification, "the mass fraction (%) of particles having a particle size of 150 μm or more and less than 300 μm" refers to the mass fraction (%) of particles that pass through a sieve with a 300 μm mesh when a sieve with a 300 μm mesh is used and remain on a sieve with a 150 μm mesh when a sieve with a 150 μm mesh is used, relative to the entire calcium carbonate fine powder.

[0026] The content of the calcium carbonate fine powder is preferably 5 to 40 parts by mass, more preferably 10 to 35 parts by mass, further preferably 13 to 30 parts by mass, and particularly preferably 15 to 25 parts by mass, relative to 100 parts by mass of Portland cement. By having the content of the calcium carbonate fine powder in such a range, it becomes possible to ensure a sufficient time for applying the mortar composition, and there is a tendency that good strength can be obtained.

[0027] The fine aggregate can be suitably selected from sands such as silica sand, river sand, land sand, sea sand, crushed sand, etc. The particle size of the fine aggregate is preferably such that the mass fraction (%) of coarse particles having a particle size of more than 1.2 mm is less than 15% in 100% fine aggregate.

[0028] The particle size of fine aggregate can be determined in accordance with the sieve test method for aggregate specified in JIS A 1102: 2014. In addition, in this specification, "coarse particles having a particle size of more than 1.2 mm" refers to the mass fraction (%) of fine aggregate that remains on a sieve with a nominal mesh size of 1.2 mm.

[0029] When the fine aggregate contains 15% or more of coarse particles having a particle size of more than 1.2 mm, the surface precision of the hydraulic composition tends to decrease. There is no particular lower limit for the coarse particles, and the coarse particles may be 0%. To obtain excellent surface precision, the coarse particles in the fine aggregate are more preferably 0 to 13%, even more preferably 1 to 11%, and particularly preferably 2 to 10%.

[0030] In addition, the mass fraction (%) of the fine aggregate retained in each sieve is preferably 45 to 60% for a sieve opening of 0.6 mm, 70 to 85% for a sieve opening of 0.425 mm, 85 to 97% for a sieve opening of 0.3 mm, and 93 to 100% for a sieve opening of 0.15 mm, more preferably 46 to 59% for a sieve opening of 0.6 mm, 71 to 84% for a sieve opening of 0.425 mm, 86 to 96% for a sieve opening of 0.3 mm, and 94 to 100% for a sieve opening of 0.15 mm, and even more preferably 47 to 58% for a sieve opening of 0.6 mm, 72 to 83% for a sieve opening of 0.425 mm, 87 to 95% for a sieve opening of 0.3 mm, and 95 to 100% for a sieve opening of 0.15 mm. By keeping the mass fraction (%) of fine aggregate retained on each sieve in such a range, better surface precision tends to be obtained.

[0031] The content of the fine aggregate is preferably 60 to 200 parts by mass, more preferably 80 to 180 parts by mass, further preferably 90 to 160 parts by mass, and particularly preferably 100 to 140 parts by mass, relative to 100 parts by mass of Portland cement. By having the content of the fine aggregate within such a range, it is possible to obtain a mortar hardened body having superior workability and, when integrated with a concrete structure, a compressive strength equal to or greater than that of the concrete structure.

[0032] The inorganic expanding material is preferably a quicklime-gypsum expanding material. The expanding material may be a combination of two types of expanding material, an expanding material A having a quicklime content of less than 40% by mass and an expanding material B having a quicklime content of 40% by mass or more. The quicklime content of the expanding material A is preferably 30% by mass or less, and the quicklime content of the expanding material B is preferably 50% by mass or more. In addition, the mixing ratio of the expanding material A and the expanding material B is preferably in the range of expanding material A:expanding material B=55:45 to 95:5 (parts by mass) when the total of the expanding materials is 100 parts by mass, and more preferably in the range of expanding material A:expanding material B=60:40 to 90:10. By having the mixing ratio of the inorganic expanding material in such a range, it tends to be possible to form a mortar hardened body having excellent dimensional stability and sufficient adhesion durability when integrated with a concrete structure.

[0033] Here, the amount of quicklime in the inorganic expansive material can be obtained by the glycerin-alcohol method (Method B) of JCAS I-01-1997 "Quantitative method for free calcium oxide." Furthermore, the quicklime and gypsum contained in the inorganic expansive material can be confirmed by powder X-ray diffraction measurement.

[0034] The content of the inorganic expansive material is preferably 4 to 20 parts by mass, more preferably 6 to 17 parts by mass, further preferably 8 to 15 parts by mass, and particularly preferably 10 to 13 parts by mass, relative to 100 parts by mass of Portland cement. By having the content of the inorganic expansive material within such a range, it tends to be possible to form a mortar hardened body that is excellent in dimensional stability and has excellent adhesion durability when integrated with a concrete structure.

[0035] As the fluidizing agent, any commercially available fluidizing agent that also has a water-reducing effect, such as formaldehyde condensation products of melamine sulfonic acid, casein, calcium caseinate, polycarboxylic acid-based, polyether-based, or polyether polycarboxylic acid-based fluidizing agents, can be used regardless of type.

[0036] The content of the superplasticizer is preferably 0.02 to 0.20 parts by mass, more preferably 0.03 to 0.15 parts by mass, further preferably 0.04 to 0.12 parts by mass, and particularly preferably 0.05 to 0.10 parts by mass, relative to 100 parts by mass of Portland cement. When the content of the superplasticizer is within such a range, trowel application property and adhesiveness tend to be improved.

[0037] The shrinkage reducing agent can be suitably added with a known shrinkage reducing agent. Examples of the shrinkage reducing agent include substances having an alkylene oxide polymer in the skeleton of the chemical structure. Such substances can be suitably selected and added from generally known substances such as polyalkylene glycols such as polypropylene glycol and poly(propylene·ethylene) glycol, polyoxyalkylene ethers, and alkoxypoly(propylene·ethylene) glycols having 1 to 6 carbon atoms. By adding an appropriate amount of shrinkage reducing agent, the dimensional stability of the hardened mortar can be improved.

[0038] The content of the shrinkage reducing agent is preferably 0.5 to 5.0 parts by mass, more preferably 0.7 to 4.0 parts by mass, further preferably 0.9 to 3.5 parts by mass, and particularly preferably 1.0 to 3.0 parts by mass, relative to 100 parts by mass of Portland cement. By having the content of the shrinkage reducing agent in such a range, it is possible to further reduce long-term drying shrinkage.

[0039] The defoaming agent may be a known substance such as a synthetic substance such as a silicone-based, alcohol-based, or polyether-based substance, or a natural substance derived from a plant. From the viewpoint of price and availability, the defoaming agent is preferably a polyether-based defoaming agent. By using the defoaming agent, the workability of the hydraulic composition can be improved.

[0040] The content of the antifoaming agent is preferably 0.02 to 0.20 parts by mass, more preferably 0.03 to 0.16 parts by mass, still more preferably 0.04 to 0.13 parts by mass, and particularly preferably 0.05 to 0.10 parts by mass, relative to 100 parts by mass of Portland cement. By having the content of the antifoaming agent in such a range, workability tends to be further improved.

[0041] The re-emulsified resin powder may be a powder produced by a known production method. The re-emulsified resin powder may be a re-emulsified resin powder obtained by removing the solvent by a method such as spraying an aqueous polymer dispersion or freeze-drying, and then drying. The re-emulsified resin powder may be a powder in which an anti-blocking agent is attached to the surface of the re-emulsified resin powder.

[0042] The re-emulsified resin powder is preferably a powder containing a styrene / acrylic copolymer resin as a main component, which tends to further improve adhesion durability.

[0043] The content of the re-emulsified resin powder is preferably 2.0 to 10.0 parts by mass, more preferably 2.5 to 9.0 parts by mass, further preferably 2.8 to 8.0 parts by mass, and particularly preferably 3.0 to 7.0 parts by mass, relative to 100 parts by mass of Portland cement. By having the content of the re-emulsified resin powder in such a range, the adhesive durability tends to be further improved.

[0044] The alkyl silicone resin-based water repellent may be, for example, a water repellent having an organopolysiloxane as an active ingredient, which has a siloxane structure having a bond between a silicon atom and an oxygen atom as a main chain and has an alkyl group on the silicon atom constituting the main chain. The number of carbon atoms in the alkyl group is not particularly limited, but is preferably 1 to 12. The alkyl silicone resin-based water repellent is preferably a water repellent having an organopolysiloxane derived from triethoxyoctylsilane as an active ingredient. The alkyl silicone resin-based water repellent may be a commercially available product.

[0045] By including an alkyl silicone resin-based water repellent in a hydraulic composition, the hydraulic composition tends to have excellent strength development and water absorption suppression. Although the reason for such an effect is not necessarily clear, the present inventors believe that an effect similar to that of a silane coupling agent that bonds inorganic materials and organic materials occurs.

[0046] The alkyl silicone resin-based water repellent may contain, in addition to the active ingredient, an auxiliary agent such as ethanol.

[0047] The content of the active ingredient in the alkyl silicone resin-based water repellent is preferably 40% by mass or more, more preferably 51% by mass or more, even more preferably 55% by mass or more, and particularly preferably 60% by mass or more, based on the total mass of the water repellent. When the content of the active ingredient is within such a range, it tends to be possible to more reliably avoid a decrease in the unit volume mass of the mortar composition.

[0048] The content of the alkyl silicone resin-based water repellent is preferably 0.01 to 3.00 parts by mass, more preferably 0.03 to 2.50 parts by mass, further preferably 0.05 to 2.00 parts by mass, and particularly preferably 0.1 to 1.95 parts by mass, relative to 100 parts by mass of Portland cement. By having the content of the alkyl silicone resin-based water repellent in such a range, the amount of water absorption is suppressed, excellent strength expression is more assured, and compressive strength as well as bending strength tends to be sufficiently maintained.

[0049] <Mortar composition> The mortar composition of one embodiment can be prepared by mixing and kneading the above-mentioned cement composition and water. A preferred embodiment of the mortar composition of this embodiment will be described below. The mortar composition of this embodiment can be suitably used as a repair mortar. When preparing the mortar composition, the flow value and unit volume mass of the mortar composition can be adjusted by appropriately changing the amount of water. By changing the amount of water in this way, a repair mortar suitable for the application can be prepared. Here, the flow value is a value measured in accordance with the test method described in JIS R 5201-2015 "Physical Test Methods for Cement", and the unit volume mass is a value (unit: kg / L) measured in accordance with the test method described in JIS A 1171-2016 "Test Methods for Polymer Cement Mortar".

[0050] The amount of water to be added is preferably 13 to 23 parts by mass, more preferably 14 to 22 parts by mass, further preferably 15 to 21 parts by mass, and particularly preferably 16 to 20 parts by mass, based on 100 parts by mass of the hydraulic composition.

[0051] The flow value of the mortar composition of the present embodiment is preferably 140 to 220 mm, more preferably 150 to 210 mm, further preferably 160 to 200 mm, and particularly preferably 170 to 190 mm. When the flow value of the mortar composition is in such a range, the mortar composition tends to have better workability (good trowelability and sprayability).

[0052] The unit volume mass of the mortar composition of this embodiment is preferably 1.80 to 2.50 kg / L (liter), more preferably 1.90 to 2.40 kg / L, even more preferably 2.00 to 2.30 kg / L, and particularly preferably 2.05 to 2.25 kg / L. By having the unit volume mass of the mortar composition in such a range, it tends to be possible to obtain an appropriate compressive strength for integration with a concrete structure while maintaining good workability (good trowelability and sprayability) of the mortar composition.

[0053] <Hardened mortar> The hardened mortar body of one embodiment is a hardened body of a mortar composition, and can be obtained by hardening the above-mentioned mortar composition. A preferred embodiment of the hardened mortar body of this embodiment will be described below. The hardened mortar body of this embodiment can be suitably used as a hardened mortar body for repair. That is, the hardened mortar body of this embodiment formed by hardening the above-mentioned mortar composition has bending strength, compressive strength, and water absorption equal to or greater than those of concrete when integrated with a concrete structure.

[0054] Here, the bending strength, compressive strength and water absorption are values ​​measured in accordance with the test methods described in JIS R 5201-2015 "Physical test methods for cement."

[0055] The bending strength of the hardened mortar body of this embodiment is preferably 8N / mm 2 More preferably, it is 8.5N / mm 2 More preferably, it is 9 N / mm 2 More preferably, it is 9.5 N / mm 2 By having the bending strength of the hardened mortar body within this range, when the hardened mortar body is integrated with a concrete structure, it tends to have a strength suitable for integration, i.e., a strength equal to or greater than that of concrete.

[0056] The compressive strength of the mortar hardened body of this embodiment is preferably 20 N / mm 2 More preferably, it is 30N / mm 2 More preferably, it is 40N / mm 2 More preferably, it is 50 N / mm 2 By having the compressive strength of the hardened mortar body within this range, when the hardened mortar body is integrated with a concrete structure, it tends to have a strength suitable for integration, i.e., a strength equal to or greater than that of concrete.

[0057] The water absorption amount of the hardened mortar of this embodiment is preferably 24 g or less, more preferably 22 g or less, further preferably 20 g or less, and particularly preferably 18 g or less. When the water absorption amount of the hardened mortar is within such a range, the hardened mortar tends to have a suppressed water absorption amount when integrated with a concrete structure, and has durability suitable for integration.

[0058] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments. EXAMPLES

[0059] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples.

[0060] (1) Portland cement Ordinary Portland cement (manufactured by Ube Mitsubishi Cement Co., Ltd., Blaine specific surface area 3270 cm 2 / g) (2) Calcium carbonate fine powder (Blaine specific surface area 4098 cm 2 / g) (3) Fine aggregate Silica sand (coarse particles with a particle size of more than 1.2 mm = 3.9% by mass) (4) Inorganic expansive materials (calcium oxide-gypsum expansive materials) -Expansive material A (calcium oxide content: 29.88% by mass, X-ray diffraction peak: the diffraction angle (2θ) of the main peak derived from CaO was 37.36°, and the intensity was 7413. The diffraction angle (2θ) of the main peak derived from CaSO4 was 25.42°, and the intensity was 16333.) ·Expansive material B (quicklime content 50.46 mass%, in the X-ray diffraction peak, the diffraction angle (2θ) of the main peak derived from CaO was 37.38°, and the intensity was 19470. In addition, the diffraction angle (2θ) of the main peak derived from CaSO4 was 25.42°, and the intensity was 5980.) (5) Superplasticizer Polycarboxylic acid-based fluidizing agent (6) Shrinkage reducing agents ·Alkylene oxide shrinkage reducer (7) Defoaming agent Polyether-based defoaming agent (8)Re-emulsified resin powder Resin powder mainly composed of styrene / acrylic copolymer resin (9) Water repellent Water repellent A (alkyl silicone resin, active ingredient: 65% by weight) Water repellent B (alkyl silicone resin, active ingredient: 50% by weight) Water repellent C (aluminum stearate type) Water repellent D (calcium stearate type)

[0061] [Preparation (manufacture) of hydraulic composition] The above materials (total amount: 5 kg each) were mixed in the mixing ratios of Mixtures No. 1 to 11 shown in Tables 1 and 2 to obtain hydraulic compositions.

[0062] [Table 1]

[0063] [Table 2]

[0064] The mortar compositions of each Example and Comparative Example were prepared by mixing 1 kg of each hydraulic composition prepared at the mixing ratio shown in Tables 1 and 2 with the amount of mixing water shown in Table 3. Mixing was carried out at a low speed for 3 minutes using a Hobart mixer under conditions of a temperature of 20°C and a relative humidity of 65%.

[0065] [Method of evaluating the physical properties of mortar compositions and hardened mortar bodies] The flow value, unit volume mass, bending strength, compressive strength, and water absorption of the mortar composition or hardened mortar body prepared in each of the Examples and Comparative Examples were measured. The measurement results are shown in Table 3. Each measurement was performed by the method shown below. For Comparative Examples in which the bending strength was insufficient, the compressive strength was not measured. In Table 3, "-" means that the measurement was not performed.

[0066] (1) Flow value measurement method The flow value was measured in accordance with the test method described in JIS R 5201-2015 "Physical test methods for cement." (2) Measurement method for unit mass The unit volume mass was measured in accordance with the test method described in JIS A 1171-2016 "Test methods for polymer cement mortars." (3) Measurement method for bending strength The bending strength was measured in accordance with the test method described in JIS A 1171-2016 "Test methods for polymer cement mortars." (4) Method for measuring compressive strength The compressive strength was measured in accordance with the test method described in JIS A 1171-2016 "Test methods for polymer cement mortars." (5) Method for measuring water absorption The water absorption was measured in accordance with the test method described in JIS A 1171-2016 "Test methods for polymer cement mortars."

[0067] [Table 3]

[0068] As shown in Table 3, the mortar compositions of Examples 1 to 6, which contain a hydraulic composition containing an alkyl silicone resin-based water repellent, had sufficiently low water absorption and were superior in bending strength and compressive strength compared to the mortar compositions of Comparative Examples 1 to 5, which contain a hydraulic composition not containing an alkyl silicone resin-based water repellent. These results confirmed that the hydraulic composition and mortar composition of the present invention have good workability and are capable of forming a hardened mortar body that is excellent in strength development and water absorption suppression. [Industrial Applicability]

[0069] According to the present invention, there are provided a hydraulic composition and a mortar composition which have good workability and can form a hardened mortar having excellent strength development and water absorption suppression. Therefore, the hydraulic composition of the present invention can be suitably used for repairing a cross section of concrete.

Claims

[Claim 1] A hydraulic composition comprising portland cement, calcium carbonate fine powder, fine aggregate, an inorganic expanding agent, a fluidizing agent, a shrinkage reducing agent, an antifoaming agent, a re-emulsified resin powder and an alkyl silicone resin water repellent.

Citation Information

Patent Citations

  • Highly-durable finishing material

    JP2013095615A

  • Mortar for finishing

    JP2017114735A